The Dynamic Block Remapping Cache - Pedroni, Felipe Thomaz; Souza, Alberto F. De; Badue, Claudine (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2010)
In this paper we present a new architecture of Level 2 (L2) cache – the Dynamic Block Remapping Cache (DBRC). DBRC mimics important characteristics of virtual memory systems to reduce the impact of L2 in system performance. Similar to virtual memory systems, the DBRC uses a hierarchy of tables to map blocks of L2 cache into blocks of physical memory. It also uses a Block-TLB to speedup accesses to previously performed block translations. We verified that the benefits of full associativity and the consequent possibility of employment of global block replacement algorithms allow hit rates higher than those of equivalent standard caches. We compare DBRC with standard caches in terms of miss rate, energy consumption and impact on the instruction-level parallelism (ILP) of a simulated superscalar processor. Our results show that DBRC outperforms standard caches in terms of miss rate, energy consumption and impact on ILP.